National standards for the practice of ecological restoration in Australia - McDonald, T.; Jonson, J.; Dixon, Kingsley (Blackwell Science Inc., 2016)
The contemporary call for restoration and rehabilitation comes at a critical point in our planet’s history where human influence is all pervasive. Australia’s long and relatively uninterrupted evolutionary past means the continent possesses ancient soils and exceptionally diverse and unique biota—yet its terrestrial and marine ecosystems carry a more recent legacy of extensive and continuing environmental degradation, particularly in urban, industrial, and production landscapes and aquatic environments. Anthropogenic climate change is superimposing further pressure on ecosystems, whose vulnerability to climate change is exacerbated by other causal factors including land clearing, overharvesting, fragmentation, inappropriate management, disease, and invasive species. Degradation is so severe in most cases that it will not be overcome without active and ecologically appropriate intervention including mitigation of these causal factors and reinstatement of indigenous biodiversity. The practice of ecological restoration and rehabilitation seeks to transform humanity’s role from one where we are the agents of degradation to one where we act as conservators and healers of indigenous ecosystems. It is in this context that the National Standards for the Practice of Ecological Restoration in Australia (the “Standards”) has been prepared by the Society for Ecological Restoration Australasia (SERA) in collaboration with its 12 not-for-profit Partner and advisor organizations; all of whom, like SERA, are dedicated to effective conservation management of Australia’s indigenous ecological communities. This document identifies the need and purpose of ecological restoration and explains its relationship with other forms of environmental repair. The Standards identifies the principles underpinning restoration philosophies and methods, and outlines the steps required to plan, implement, monitor, and evaluate a restoration project to increase the likelihood of its success. The Standards are relevant to—and can be interpreted for—a wide spectrum of projects ranging from minimally resourced community projects to large-scale, well-funded industry or government projects. SERA and its Partners have produced these Standards for adoption by community, industry, regulators/government, and land managers (including private landholders and managers of public lands at all levels of government) to raise the standard of restoration and rehabilitation practice across all sectors. The document provides a blueprint of principles and the standard that will aid voluntary as well as regulatory organizations in their efforts to encourage, measure, and audit ecologically appropriate environmental repair in all land and water ecosystems of Australia.